PENGARUH GAJI DAN BEBAN KERJA TERHADAP TURNOVER KARYAWAN DI PT. ERIMA BAJA JAYA - Hilaludin; Netty Laura; Ganda Hutapea Hutapea (Universitas Kristen Indonesia, 2026)
Abstract The goal of this study is to determine the partial and simultaneous effects of two independent variables, workload and salary, on the dependent variable, employee turnover. This study collects data through a questionnaire, hence it is quantitative in nature. (kuesioner). The study's participants are PT. Erima Baja Jaya employees. This study's sample size is 36 respondents. The partial test (t-test) results show that salary (X1) has a significant negative impact on employee turnover, with a t value of 2.304 > 1.688 (t-table) and a significance value of 0.023 < 0.05. The Workload variable (X2) has a positive and significant impact on employee turnover, with a t-value of 2.195 > 1.688 and a significance value of 0.035 <0.05. Furthermore, with a computed F value of 9.919 and a significance level of 0.001, the Simultaneous Test (F-test) shows that the Workload and Salary variables have a substantial simultaneous influence on the Employee Turnover variable, whereas the F table value is 3.26. The significance level of 0.001 is smaller than 0.05, and the anticipated F value exceeds the F table value. The Adjusted R2 Coefficient of Determination test (Y) also reveals a 33.8% association between the Workload variable (X2), Salary variable (X1), and Employee Turnover. Keywords: Salary, Workload, and Turnover